2014
DOI: 10.1186/s12950-014-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide responsiveness in vocal fold fibroblasts

Abstract: BackgroundVocal fold fibroblast’s (VFF) strategic location in the lamina propria and their ability to respond to external stimuli by producing inflammatory molecules suggest their possible direct involvement in innate immunity. Toll-like receptors (TLRs) are an essential signaling component to this response, as they allow for recognition of various microorganisms, leading to subsequent induction of pro-inflammatory genes. The objective of this study was to elucidate the role of VFF in the host immune response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
8
0
2
Order By: Relevance
“…Vocal fold macrophages response to LPS may be reflective of differences across organs. Fibroblasts are the most abundant cell type in the vocal fold [ 1 ] and have been shown in vitro to activate TLR4 ligation in response to LPS, although they do not appear to produce measureable levels of TNFα, IL–12 or IL–10 cytokines in response [ 22 ]. Further work, has demonstrated that vocal fold fibroblasts can influence the function of activated macrophages when co-cultured together [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocal fold macrophages response to LPS may be reflective of differences across organs. Fibroblasts are the most abundant cell type in the vocal fold [ 1 ] and have been shown in vitro to activate TLR4 ligation in response to LPS, although they do not appear to produce measureable levels of TNFα, IL–12 or IL–10 cytokines in response [ 22 ]. Further work, has demonstrated that vocal fold fibroblasts can influence the function of activated macrophages when co-cultured together [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targets were amplified using GoTaq Hot Start Polymerase (Promega Corporation, Madison, WI) with the PTC- 200 Peltier Thermal Cycler according to the manufacturer’s protocol. Amplifications were optimized for each primer and carried out for 40 cycles as previously described [ 22 ]. Yields underwent electrophoresis on 2% agarose gel using ethidium bromide staining for visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular HMGB1 interacts with multiple cell surface receptors such as the receptor for advanced glycation end products, Toll‐like receptor (TLR) 2, and TLR 4, which in turn activates the nuclear factor‐κB (NF‐κB) signal pathway. NF‐κB is a transcription factor found in almost all mammalian cell types, including human vocal fold fibroblasts . The NF‐κB family of transcription factors plays a key role in the immune response by regulating a wide range of gene expression, including interleukins (ILs), tumor necrosis factors (TNFs), chemokines, growth factors, adhesion molecules, and inhibitors of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…To mimic the inflammatory conditions of VF injury, the following experiments were designed to treat with LTP after LPS treatment. 14 First, 30 or 60 s of LTP with/without LPS showed no toxic effects on the viability of human VF-MSCs. No significant cytotoxicity was observed in LPS-only-treated human VF-MSCs.…”
Section: Resultsmentioning
confidence: 88%